2007
DOI: 10.1038/sj.npp.1301464
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Adrenalectomy with Diurnal Corticosterone Replacement Slows Escalation and Prevents the Augmentation of Cocaine-Induced Reinstatement in Rats Self-Administering Cocaine Under Long-Access Conditions

Abstract: The loss of control over cocaine use and persistently heightened susceptibility to drug relapse that define human cocaine addiction are consequences of drug-induced neuroplasticity and can be studied in rats self-administering cocaine under conditions of daily long access (LgA) as escalating patterns of drug intake and heightened susceptibility to reinstatement. This study investigated the potential contribution of elevated glucocorticoids at the time of LgA cocaine self-administration (SA) to these behavioral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 46 publications
(61 reference statements)
4
34
0
Order By: Relevance
“…We have reported that an intact adrenal response at the time of earlier drug SA is necessary for the establishment of neuroadaptations that lead to heightened cocaine seeking Mantsch et al, 2008b). Our findings are consistent with previous reports that eliminating cocaine-induced adrenal responses during the induction phase prevents the later expression of stress-and cocaine-induced sensitization (Rouge-Pont et al, 1995;Prasad et al, 1996Prasad et al, , 1998Przegaliński et al, 2000;de Jong et al, 2007).…”
Section: Introductionsupporting
confidence: 83%
See 4 more Smart Citations
“…We have reported that an intact adrenal response at the time of earlier drug SA is necessary for the establishment of neuroadaptations that lead to heightened cocaine seeking Mantsch et al, 2008b). Our findings are consistent with previous reports that eliminating cocaine-induced adrenal responses during the induction phase prevents the later expression of stress-and cocaine-induced sensitization (Rouge-Pont et al, 1995;Prasad et al, 1996Prasad et al, , 1998Przegaliński et al, 2000;de Jong et al, 2007).…”
Section: Introductionsupporting
confidence: 83%
“…It has been suggested that escalated SA reflects the loss of control over drug use that is central to human cocaine addiction. As reported previously Mantsch et al, 2008b), ADX/C failed to alter SA before escalation (ie, on the first day of testing), consistent with reports in monkeys and human addicts that increased glucocorticoid secretion by cocaine is not necessary for its acute reinforcing effects (Broadbear et al, 1999b;Ward et al, 1999). Others have shown that complete elimination of glucocorticoids by surgical or pharmacological ADX in the absence of corticosterone replacement attenuates cocaine SA in rats (Goeders and Guerin, 1996;Deroche et al, 1997).…”
Section: Role Of Glucocorticoids In Stress-and Crf-induced Reinstatementsupporting
confidence: 72%
See 3 more Smart Citations